The Role of Russian Federation Government Policy in Addressing the Impacts of Global Climate Change - Rakuasa, Heinrich; Faris, Dzaka. A; Hidayatullah, Muh. (Nusantara Journal of Behavioral and Social Science, 2024)
This study aims to evaluate the effectiveness of the Russian Federation government's policies in addressing the impacts of global climate change. The methodology employed is a detailed literature review, which includes a thorough selection of credible sources and systematic data analysis. The main findings highlight the challenges Russia faces, such as reducing dependence on fossil fuels, managing political uncertainties, and enhancing environmental resilience. The study also examines the government's mitigation and adaptation strategies, including energy diversification, public awareness campaigns, and international collaboration. Key recommendations are provided to strengthen climate policies, invest in green technologies, and promote public and private sector participation. The conclusions emphasize the need for comprehensive policy evaluation and future planning to ensure sustainable development and effective climate action in Russia. Through these measures, Russia can significantly contribute to global efforts in reducing greenhouse gas emissions and adapting to climate change, thereby securing a sustainable future for its people and environment. Abstrak: Studi ini bertujuan untuk mengevaluasi efektivitas kebijakan pemerintah Federasi Rusia dalam menangani dampak perubahan iklim global. Metodologi yang digunakan adalah tinjauan literatur yang mendetail, yang mencakup pemilihan sumber yang kredibel dan analisis data yang sistematis. Temuan utama menyoroti tantangan yang dihadapi Rusia, seperti mengurangi ketergantungan pada bahan bakar fosil, mengelola ketidakpastian politik, dan meningkatkan ketahanan lingkungan. Studi ini juga meneliti strategi mitigasi dan adaptasi pemerintah, termasuk diversifikasi energi, kampanye kesadaran publik, dan kerja sama internasional. Rekomendasi kunci disediakan untuk memperkuat kebijakan iklim, berinvestasi dalam teknologi hijau, dan mempromosikan partisipasi sektor publik dan swasta. Kesimpulan menekankan perlunya evaluasi kebijakan yang komprehensif dan perencanaan masa depan untuk memastikan pembangunan berkelanjutan dan aksi iklim yang efektif di Rusia. Melalui langkah-langkah ini, Rusia dapat secara signifikan berkontribusi pada upaya global dalam mengurangi emisi gas rumah kaca dan beradaptasi terhadap perubahan iklim, sehingga memastikan masa depan yang berkelanjutan bagi rakyat dan lingkungannya.